Adipose gene expression profiles in Northern Finncattle, Mirandesa cattle, Yakutian cattle and commercial Holstein cattle - Ruvinskiy, Daniil; Amaral, Andreia; Weldenegodguad, Melak; Ammosov, Innokentyi; Honkatukia, Mervi; Lindeberg, Heli; Peippo, Jaana; Popov, Ruslan; Soppela, Päivi; Stammler, Florian; Uimari, Pekka; Ginja, Catarina; et al. (Scientific Reports)
The drastic change in global climate has led to in-depth studies of the geneticresources of native cattle adapted to challenging environments. Native cattle breeds may harbor unique genetic mechanisms that have enabled them adapt to their given environmental conditions. Adipose tissues are key factors in the regulation of metabolism and energy balance and are crucial for the molecular switches needed to adapt to rapid environmental and nutritional changes. The transcriptome landscape of four adipose tissues was used in this study to investigate the differential gene expression profiles in three local breeds, Yakutian cattle (Sakha Republic), Northern Finncattle (Finland), Mirandesa cattle (Portugal) and commercial Holstein cattle. A total of 26 animals (12 cows, 14 bulls) yielded 81 samples of perirenal adipose tissue (n = 26), metacarpal adipose tissue (n = 26), tailhead adipose tissue (n = 26) and prescapular adipose tissue (n = 3). More than 17,000 genes were expressed in our dataset. Principal component analysis of the normalized expression profiles revealed a differential expression profile of the metacarpal adipose tissue. We found that the genes upregulated in the metacarpal adipose tissue of Yakutian cattle, such as NR4A3, TEKT3, and FGGY, were associated with energy metabolism and response to cold temperatures. In Mirandesa cattle, the upregulated genes in perirenal adipose tissue were related to immune response and inflammation (AVPR2, CCN1, and IL6), while in Northern Finncattle, the upregulated genes appeared to be involved in various physiological processes, including energy metabolism (IGFBP2). According to the sex-based comparisons, the most interesting result was the upregulation of the TPRG1 gene in three tissues of Yakutian cattle females, suggesting that adaptation is related to feed efficiency. The highest number of differentially expressed genes was found between Yakutian cattle and Holstein, several of which were associated with immunity in Yakutian cattle, indicating potential differences ...